Cultural Intelligence as a Moderator of Factors Affecting the Performance of Teachers in Remote Areas, Indonesia - Tria Ina Utari; Yandi Wagola; Adam Bin Haji Jait (Yayasan Keluarga Guru Mandiri, 2025)
Remote environments are far from urban areas, which have many essential services. The absence of important goods and services in remote areas is described as equivalent to the typically poor working and living conditions. Isolation implies that teachers have limited interaction with other teachers who can share resources and teaching practices to improve their performance. This research aims to fill the gap in understanding teachers' adaptability by exploring cultural intelligence as a moderator of the factors influencing their performance in remote areas. The research employed a quantitative approach using path analysis. Participants in the study are high school teachers in West Seram. Data were collected through observation, questionnaires, and interviews. There were indications of positive teacher responses, with an average score of 4.42. The results show that self-efficacy and work discipline positively affect cultural intelligence but do not significantly affect overall teacher performance. Cultural intelligence considerably impacts teachers' self-efficacy in remote areas, making it valuable to study and continue developing their abilities and integrating with the surrounding environment.